The Shortest Road Algorithm Approach In Determining The Route Of Solid Waste Collection Vehicles: The Case Of Manisa 75. Yıl Neighborhood - Gokcan, Ali Osman; Cotelı, Resul; Tanyıldızı, Erkan (My University, 2020)
Many studies have been conducted in recent years to solve the Shortest Route Problem, and the solutions produced as a result of these studies are used in all aspects of everyday life. Package distribution of cargo companies, school services leaving students home, bank branches collecting money and forwarding it to the central bank, municipalities collecting wastes, and bread companies distributing bread to bakery markets, and similar transportation services in which vehicle routing is needed make use of these solutions. Some algorithms related to the Shortest Route Problem were examined in this article, and among these, the Dijkstra Algorithm was applied to a real example problem. In this example, 75. Yıl Neighborhood of Yunus Emre District of Manisa Province was modeled with the Graph Data Model, and the best road destination for solid waste collection vehicles was determined. Based on the results obtained, it was determined that the Dijkstra Algorithm identified the shortest route successfully.
Keywords: Shortest path algorithm; vehicle routing; shortest road; graph model